Aging effect of plasma-treated carbon surfaces: An overlooked phenomenon. (November 2020) - Mendez-Linan, Jose I.; Ortiz-Ortega, Euth; Jimenez-Moreno, Martin F.; Mendivil-Palma, Maria I.; Martínez-Guerra, Eduardo; Aguirre-Tostado, Francisco S.; Martinez-Chapa, Sergio O.; Hosseini, Samira; Madou, Marc J.
Abstract: Carbon surfaces become significantly activated with plasma treatment enhancing the surface energy, wettability, and bio-conjugation. However, the activated surfaces are influenced by aging effect or reorientation phenomenon, a rarely reported occurrence, that refers to the loss of surface activity with time. Generated plasma-activated surface functional groups suffer from a brief shelf life as they reorient themselves to occupy lower states of energy. This study thoroughly assesses plasma-treated pyrolyzed carbon platforms with O2, N2, and Ar plasma radiations over 3 weeks. Pristine, immediately treated, and aged carbon samples were analyzed by SEM, AFM, WCA, and XPS to observe physical and chemical changes of the surfaces. Moreover, the electrochemical analyses demonstrated radical alterations of the surface characteristics immediately after the treatment; an activation which did not last long regardless of the plasma choice. With time, clear signs of surface inactivation were recorded manifesting in the form of decreased roughness, increased water contact angle, and major alterations of surface chemical composition, capacitance, and resistance. Our observations confirm that the plasma-treated carbon samples return to the pristine surface characteristics within a brief period of time thus demonstrating the loss of surface activity irrespective of the treatment choice. Graphical abstract: Image 1